Bibliometric Analysis of Trends in Risk Factors in Melasma - Yuli Wahyu Rahmawati; Ali Mustofa (Jurnal Sains dan Kesehatan, 2026)
Risk factors for melasma have been identified at several points such as the use of birth control pills, cosmetics, sun exposure, estrogen therapy, decreased thyroid and ovarian function, ovarian tumors, nutrition, drugs that are classified as phototoxic or photoallergic, and epilepsy drugs. This article aims to determine the incidence of melasma and its risk factors. This study uses articles collected from the Google Scholar database. The data collection step uses the keyword "Risk Factor Melasma" according to the title and keyword criteria. The articles used are publications in the 2018-2023 year range. The stages of analysis are carried out using VOSviewer software for visualization and trend analysis in the form of bibliometric maps. The bibliometric approach was applied to identify publication patterns, research developments, and relationships among topics related to melasma risk factors. Based on the visualization results, 100 selected documents were published within 5 years, from 2018 to 2023. The findings provide an overview of the main research trends and contribute to a better understanding of the incidence of melasma and the factors associated with its occurrence